Development of a Highly Densified Magnetic Sheet for Inductors and Advanced Processes through Silane Surface Treatment of Fe Nanopowder - Taegyu Lee; Hyeonjin Jung; Yeonghwan Song; Seungchan Cho; Dong-Hyun Kim; Yangdo Kim; Yoon-Seok Lee; Yongho Park; Moonhee Choi (Applied Sciences, 2020)
For developing subminiature and highly integrated multilayer inductors, soft magnetic powder was used; however, its ferrite magnetic component is characterized by high resistivity and reduced direct current saturation, leading to the deterioration of the inductor under high currents. Therefore, herein, to improve the electromagnetic properties of thin-film inductors, Fe nanopowder was used to increase the volume fraction of magnetic sheets. Surface treatment was performed by using silane coupling agents, which improved the bonding strength and dispersibility of the Fe nanopowder with a heterogeneous epoxy binder. For uniform surface treatment on the nanopowder, the silane-treated powder was aged for 24 h, at a temperature of 3 °C. The surface-treated Fe nanopowder was used with a mixing ratio of the soft magnetic powder (coarse:fine:nano) of 7:2.5:0.5 wt.%; this was successful in producing a flexible and highly densified magnetic sheet. As a result, the volume fraction of the magnetic sheet for thin-film inductors to which a low-temperature aging-treated nanopowder was applied was significantly improved.